Using Flame Spraying Technology in the Manufacture of Tools with Abrasive-Containing Polymer Coating - Marat A. Belotserkovsky; Anastasia O. Grishchenko; Igor I. Taran (Механика машин, механизмов и материалов, 2024)
The possibility of forming abrasive-containing coatings based on ultra-high molecular weight polyethylene by flame spraying has been studied. Using the method of differential scanning calorimetry, it is shown that in the process of gas-flame spraying, particles do not reach the temperature range of thermal-oxidative destruction, and the basic structure of UHMWPE is preserved. The dependence of the adhesion strength of abrasive-containing coatings on their cooling rate and the composition of the propane-air mixture has been determined. Spraying modes have been determined for coatings containing abrasive particles from 0.3 to 1.2 mm, and coatings with abrasive from 10 to 100 μm. It is advisable to use the resulting coatings in the manufacture of various abrasive tools. It has been established that the introduction of a nanosized filler in the form of powdered diamond-containing charge ShA-A into the sprayed abrasive-polymer mixture makes it possible to increase the mechanical characteristics of coatings.